Synthesis and Characterization of Iron(III), Manganese(III) and Chromium(III) Complexes with N,N'-Propylene-bis(3-carboxypropenamide) - Radhakrishnan Namboori, C.G.; Krishnan, G. (Asian Journal of Chemistry, 2016)
A series of thirteen complexes of trivalent transition metal ions, viz., Fe(III), Mn(III) and Cr(III) with a polydentate ligand N,N'-propylene-bis(3-carboxypropenamide) and various anions such as chloride, bromide, nitrate, thiocyanate, perchlorate and acetate have been synthesized and characterized. The analytical data include elemental analysis, molecular weight determinations, molar conductance, magnetic moment, infrared spectra and X-ray diffraction. The spectral studies suggest that ligand behaves as divalent tetradentate, coordinating through two-amido nitrogen and two oxygen atoms of the carboxylate groups and the anions act as unidentate ligand.